Does employment security modify the effect of housing affordability on mental health?. (December 2016) - Bentley, Rebecca; Baker, Emma; LaMontagne, Anthony; King, Tania; Mason, Kate; Kavanagh, Anne
Abstract: This paper uses longitudinal data to examine the interrelationship between two central social determinants of mental health – employment security and housing affordability. Data from ten annual waves of the longitudinal Household, Income and Labour Dynamics in Australia (HILDA) survey (which commenced in 2000/1 and is ongoing) were analysed using fixed-effects longitudinal linear regression. Change in the SF-36 Mental Component Summary (MCS) score of working age individuals (25–64 years) (51, 885 observations of 10, 776 people), associated with changes in housing affordability was examined. Models were adjusted for income, age, survey year, experience of serious injury/illness and separation/divorce. We tested for an additive interaction between the security of a household's employment arrangements and housing affordability. People in insecurely employed households appear more vulnerable than people in securely employed households to negative mental health effects of housing becoming unaffordable. In adjusted models, people in insecurely employed households whose housing became unaffordable experienced a decline in mental health (B=−1.06, 95% CI −1.75 to −0.38) while people in securely employed households experienced no difference on average. To progress our understanding of the Social Determinants of Health this analysis provides evidence of the need to bridge the (largely artificial) separation of social determinants, and understand how they are related. Highlights: Two main sources of socio-economic inequality in neo-liberal economies are employment security and housing affordability. We understand little of their joint impact on mental health. We found that insecurely employed households experience negative mental health effects of unaffordable housing. This negative impact was not observed for securely employed households. Our findings support more targeted housing affordability interventions.